Spectral Methods for Monitoring Transformer Equipment State of Paper Insulation - Kozlov V.K.; Kurakina O.E.; Sabitov A.H.; Nigmatullina G. F.; Salyakhutdinov R. A. (Problems of the Regional Energetics, 2022)
The insulation of an oil-filled transformer is based on materials of organic origin - oil and wood pulp. The state of insulation is a key factor in the reliable operation of a power equipment, and much attention is paid to the insulation state assessment by researchers. To assess the cellulose insulation state, indicators such as the degree of polymerization and paper moisture are deter-mined. The existing methods for determining the moisture content and the degree of polymeriza-tion of a paper insulation have disadvantages, as they require a complex process of sampling the insulation, which is a time-consuming operation. The purpose of the work is to develop new methods for determining the moisture content and the degree of polymerization of the paper in-sulation of a power transformer. This goal is achieved by obtaining the reflection spectra of the paper insulation samples and constructing two correlation lines to determine the degree of polymerization and humidity. The most significant result of the article is the establishment of the dependence of the reflection coefficient of the paper on the concentration of water exceeding 4% and the position of the minimum in the reflection spectrum of paper insulation on the degree of polymerization. The significance of the obtained results lies in the fact that the optical method for determining the moisture content and the degree of polymerization of paper insulation using the constructed correlation lines is highly accurate and does not require the use of additional re-agents and complex calculations.